Pirates of the purple dawn - Abbott, Tony.; Fitzgerald, Royce (New York : Scholastic, 2007)
Everything in Droon is changing. Lord Sparr has disappeared. Ko and Gethwing have fled to the Dark Lands. And an old villain is back, Ving, leader of the Hawk Bandits! This time, he has his twin sister in tow, along with her band of wicked pirates.
"A Little Apple paperback."
Accelerated Reader AR
Keywords: Droon (Imaginary place) -- Fiction; Wizards -- Fiction; Magic -- Fiction; Fantasy fiction